2020
DOI: 10.4236/jss.2020.810003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Workplace Bullying on Employees’ Turnover Intention: The Role of Self-Esteem

Abstract: The purpose of this study is to investigate the role of self-esteem in the relationship between workplace bullying and turnover intention in China. Basing on 215 samples, this study examined the relationship among workplace bullying, self-esteem and employees' turnover intention. The results show that: self-esteem is negatively related to the probability of reporting oneself as a target of workplace bullying; workplace bullying is an excellent predictor of employees' turnover; self-esteem plays a moderating ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This is because self-esteem is a vital personality variable that impacts individuals’ behaviors and plays a significant role in the occurrence of WB (Bowling et al, 2010). The literature suggests that individuals with low self-esteem possess poorer coping abilities and are less resilient which could make them targets of WB (Li et al, 2020). In an organizational context, employees with higher self-esteem display a stronger sense of performance and may be less receptive of adverse effects compared to those with low self-esteem (Paul & Devi, 2020; PM et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because self-esteem is a vital personality variable that impacts individuals’ behaviors and plays a significant role in the occurrence of WB (Bowling et al, 2010). The literature suggests that individuals with low self-esteem possess poorer coping abilities and are less resilient which could make them targets of WB (Li et al, 2020). In an organizational context, employees with higher self-esteem display a stronger sense of performance and may be less receptive of adverse effects compared to those with low self-esteem (Paul & Devi, 2020; PM et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high selfesteem are more likable, build better relationships, and leave better impressions compared to individuals with low self-esteem who are uncertain about themselves and struggle to maintain satisfying relationships which leads them to experience more rejection and become a target of WB (Brown, 2010). In the same vein, Li et al (2020), found a significant relationship between low self-esteem and the higher likelihood of reporting oneself as a target of WB.…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…Ekici and Beder (2014) report that workplace harassment leads to poor work attitudes, low performance and decreased productivity. Moreover, (Li et al, 2020) relate the experience with poor confidence and low self-esteem. Hellstrom et al (2015), bullying is also a common source of harassment and leads to the development of an unpleasant workplace culture.…”
Section: Workplace Harassmentmentioning
confidence: 99%
“…Research framed by the feminist perspective may have elevated vigilance and awareness of the hidden nature of LV and incivility within nurse groups [ 14 ]. Previous research has been carried out on the personalities and behaviors of people who are prone to workplace violence victimizations [ 3 , 15 ]. For example, those with low self-esteem are likely to become victims of workplace violence [ 15 ] and those who are interpersonally demanding and difficult to get along with others tend to become targets of aggression from other organizational members [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has been carried out on the personalities and behaviors of people who are prone to workplace violence victimizations [ 3 , 15 ]. For example, those with low self-esteem are likely to become victims of workplace violence [ 15 ] and those who are interpersonally demanding and difficult to get along with others tend to become targets of aggression from other organizational members [ 16 ]. The underlying perspective that some victims are to blame for their victimization may have legitimized workplace violence to a certain extent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%